Community, Distribution, and Ecological Roles of Estuarine Archaea - Zou, Dayu; Liu, Hongbin; Li, Meng (Frontiers in Microbiology, 2020)
Archaea are diverse and ubiquitous prokaryotes present in both extreme and moderate environments. Estuaries, serving as links between the land and ocean, harbor numerous microbes that are relatively highly active because of massive terrigenous input of nutrients. Archaea account for a considerable portion of the estuarine microbial community. They are diverse and play key roles in the estuarine biogeochemical cycles. Ammonia-oxidizing archaea (AOA) are an abundant aquatic archaeal group in estuaries, greatly contributing estuarine ammonia oxidation. Bathyarchaeota are abundant in sediments, and they may involve in sedimentary organic matter degradation, acetogenesis, and, potentially, methane metabolism, based on genomics. Other archaeal groups are also commonly detected in estuaries worldwide. They include Euryarchaeota, and members of the DPANN and Asgard archaea. Based on biodiversity surveys of the 16S rRNA gene and some functional genes, the distribution and abundance of estuarine archaea are driven by physicochemical factors, such as salinity and oxygen concentration. Currently, increasing amount of genomic information for estuarine archaea is becoming available because of the advances in sequencing technologies, especially for AOA and Bathyarchaeota, leading to a better understanding of their functions and environmental adaptations. Here, we summarized the current knowledge on the community composition and major archaeal groups in estuaries, focusing on AOA and Bathyarchaeota. We also highlighted the unique genomic features and potential adaptation strategies of estuarine archaea, pointing out major unknowns in the field and scope for future research.